Drugs that inhibit TMEM16 proteins block SARS-CoV-2 spike-induced syncytia - Braga, Luca; Ali, Hashim; Secco, Ilaria; Chiavacci, Elena; Neves, Guilherme; Goldhill, Daniel; Penn, Rebecca; Jimenez-Guardeño, Jose Manuel; Ortega-Prieto, Ana María; Bussani, Rossana; Cannata, Antonio; Rizzari, Giorgia; et al. (Springer Nature, 2021)
COVID-19 is a disease with unique characteristics that include lung thrombosis1, frequent diarrhoea2, abnormal activation of the inflammatory response3 and rapid deterioration of lung function consistent with alveolar oedema4. The pathological substrate for these findings remains unknown. Here we show that the lungs of patients with COVID-19 contain infected pneumocytes with abnormal morphology and frequent multinucleation. The generation of these syncytia results from activation of the SARS-CoV-2 spike protein at the cell plasma membrane level. On the basis of these observations, we performed two high-content microscopy-based screenings with more than 3,000 approved drugs to search for inhibitors of spike-driven syncytia. We converged on the identification of 83 drugs that inhibited spike-mediated cell fusion, several of which belonged to defined pharmacological classes. We focused our attention on effective drugs that also protected against virus replication and associated cytopathicity. One of the most effective molecules was the antihelminthic drug niclosamide, which markedly blunted calcium oscillations and membrane conductance in spike-expressing cells by suppressing the activity of TMEM16F (also known as anoctamin 6), a calcium-activated ion channel and scramblase that is responsible for exposure of phosphatidylserine on the cell surface. These findings suggest a potential mechanism for COVID-19 disease pathogenesis and support the repurposing of niclosamide for therapy.
Keywords: Virología; Virus; Virology; SARS-CoV-2; COVID-19